Farmers’ Acuity on Climate Change in the Central Dry Zone of Karnataka - N. Ashoka,; M. Harshavardhan, Shivanand Hongal, Shankar Meti, R. Raju, Ganeshgouda I. Patil, N. Shashidhara, (Indian Journal of Extension Education, 2022)
To counteract the vulnerability results from climate change, it is critical to understand farmers’ viewpoints. In Karnataka, farmers’ perspectives, implications, adaptive measures, and barriers were investigated in 2021 by collecting the data from farmers using a multistage random sample technique. Farmers witnessed significant changes in temperature, rainfall distribution, the emergence of new plant pests and infirmity over time as a result of the introduction of new cultivars/crops, and the occurrence of drought/flood, according to the data. Crop harvests were inconsistent, depleted common property resources, and costs had risen as a result. Cultivation of stress-tolerant cultivars, drilling bore wells, novel plant protection molecules, changing sowing/harvesting dates, and water-saving techniques were among the adaptation strategies. Climate adaptation challenges in the region included high-cost farm inputs for climate-smart agriculture, labour scarcity, lack of shared water resources, and knowledge gaps. For the best results, adaptation strategies should be implemented “collectively” rather than “individually”. Weather-based Crop insurance must be marketed with assured indemnity.